From Transformative Hope to Political Reality : A Conceptual Analysis of Post-Pandemic Government Agendas in Europe - Vogt, Henri; Värttö, Mikko (Helsinki University Press, 2025)
It is easy to discern an inherently optimistic outlook in much of the COVID-19 literature. The pandemic perhaps represents an opportunity to redesign the existing parameters of society or even initiate new forms of the social contract. This article seeks to examine to what extent, and in which ways, post-pandemic official political agenda-setting realistically reflects these hopes. Through a comprehensive conceptual framework consisting of ethical, pragmatic, contractual and temporal sets of notions, the article analyses post-pandemic governmental programmes and prime ministers’ speeches in six European countries, paying attention to general descriptions of the world, issues of security in the context of multiculturalism, as well as work and resilience. The article’s main argument contends that similarities prevail across the countries, implying a functionally shared European polity informed by a general crisis modus, but these similarities do not contain any profound transformative elements with regard to future policies or societal developments.